Diketopyrrolopyrrole (DPP)-Based Materials and Its Applications: A Review - Bao, Wei Wei; Li, Rui; Dai, Zhi Cheng; Tang, Jian; Shi, Xin; Geng, Jie Ting; Deng, Zhi Feng; Hua, Jing (Frontiers in Chemistry, 2020)
Diketopyrrolopyrrole (DPP) and its derivatives have been widely studied in the past few years due to its intrinsic physical and chemical properties, such as strong electron-withdrawing, deep color, high charge carrier mobility, strong aggregation, good thermal-/photo-stability. In the 1970s, DPP was developed and used only in inks, paints, and plastics. Later, DPP containing materials were found to have potential other applications, typically in electronic devices, which attracted the attention of scientists. In this feature article, the synthesis pathway of DPP-based materials and their applications in organic field-effect transistors, photovoltaic devices, sensors, two photo-absorption materials, and others are reviewed, and possible future applications are discussed. The review outlines a theoretical scaffold for the development of conjugated DPP-based materials, which have multiple potential applications.